2022
DOI: 10.1787/b19f5af7-en
|View full text |Cite
|
Sign up to set email alerts
|

Teacher professional identity

Abstract: This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. 2  EDU/WKP(2022)5 TEACHER PROFESSIONAL IDENTITY: HOW TO DEVELOP AND SUPPORT IT IN TIMES OF CHANGE Unclassified OECD EDUCATION WORKING PAPERS SERIESOECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The four longitudinal themes we have presented show how teachers grew in their frustrations about the uncertainties they experienced and in their concern for pupils, all while becoming increasingly exhausted and less satisfied by the job of teaching in these difficult circumstances. Indeed, these changing and intensified individual, professional and contextual factors appear to have clearly affected teachers' professional identities (Suarez & McGrath, 2022 ). In turn, this appears to have affected their behaviours and attitudes and their reflections on the educational system, its future and their place within it.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The four longitudinal themes we have presented show how teachers grew in their frustrations about the uncertainties they experienced and in their concern for pupils, all while becoming increasingly exhausted and less satisfied by the job of teaching in these difficult circumstances. Indeed, these changing and intensified individual, professional and contextual factors appear to have clearly affected teachers' professional identities (Suarez & McGrath, 2022 ). In turn, this appears to have affected their behaviours and attitudes and their reflections on the educational system, its future and their place within it.…”
Section: Discussionmentioning
confidence: 99%
“…The high‐, low‐ and turning‐point scenes that the participants chose to share with us showed that there were multiple factors contributing to their experiences of being a teacher throughout this time. Contextual factors, including the professional and political environments, can affect teachers' professional identity (Beijaard et al, 2004 ; Suarez & McGrath, 2022 ) and it was clear in the stories participants told us that such factors clearly affected how they viewed their profession and their responsibilities. It was clear in our data that the participants saw themselves as planners with strong personal and professional needs to be in control and to work in a structured environment with a clear routine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations